(3gd GdcJGH GdeOQSj jYJHQ Gdjhe eSGjQG dYUQg?s - (3GdQhGOj, fYjes ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2007)
(3Ef JSGQY MQcI GdJWhQ aj GdeLJeY hNGUI aj eLGd GdJQHjI eY cd eG CJJ Hg GdJcfhdhLjG aj gPG GdeLGd jDqOj Gdi JZqjQ aj GdKbGaI HeYfGgG GdhGSY, eeG jLYd GdcJGH GdeOQSqj aj JZqjQ OGFe eQJHWq HJWqhQ hGROjGO GdeYQaI GdeSJeQqjf, hjLYd HGdJGdj eRGL GdJdejP hSdhcg aj JZqjQ eSJeQ(B. (3gd ef Gdeecf, hGdMGdI gPg, GdGYJeGO Ydi GdcJGH GdeOQSj GdhQbj ceUOQ hMjO ddeYQaI HGdfSHI ddeYde hGdeJYde? Ce Cqfg hSjdI JVGa GdjgG hSGFd CNQi? gd jdqHj HTcdg GdMGVQ MGLGJ GdeJYde GdPj GYJGO GdUhJ hGdUhQI hGdMQcI HGdGVGaI Gdi GdfU GdeSehY hGdecJhH? gd JJZqjQ YfO Pdc hXGFa GdcJGH GdeOQSj GdhQbj? ddELGHI Yf GdJSGDdGJ GdeWQhMI, CLQjoJ GNJHGQjf eSJNOekG GdWQjbI GdYjGOqjI (B(Clinique): (3GdChd Md eSCdI QjGVqjI, JJYdb Heaghe GdWQM hGdKGfj jJYdb HJMhjd fU eSCdI QjGVqjI ecJhHI Edi QSe gfOSj eSqWM(B. (3GdgOa ef GdJLQHI ebGQfI hSjdJjf GdChdi JYJeO Ydi GdcJGH GdeOQSj GdhQbj, hGdKGfjI JYJeO hSjdI GdcJQhfjI(B. (3CTGQJ GdfJGFL Edi hLhH EYGOI GdfXQ HeGgqjI GdcJGH GdeOQSj GdhQbj hebGQHI Tcd eG ef GdcJGH GdQbej djJaGYd eY GdcJGH GdJbdjOj eJjMkG ddeJYde aQUI gGqeI dJdHjI MGLGJ GdJdejP GdTNUqjI hGdeLJeYqjI GdMGdqjI cGdSQYI hGdOqbI aj GdJfajP hQHW GdeYdheGJ heTGgOI GdJZjjQ GdMGUd (B((Visualisation (3hGdYed HehLH hJjQI (B(Rythme) (3NGqUI HGdJdejP hJbjje eHGTQ dfJGFL Yedg hZjQ Pdc(B. (3gPg GdJLQHI ChMJ JQGLYkG HaGYqdjI GdcJGH GdhQbj hhXjaJg GdJYdjeqjI, GdKbGaqjI hYdGbJg HGdJZjjQ GdeLJeYjs
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Livres Scolaires; Textbooks; (3GdcJGH GdeOQSjs